Pinecone 1983 - Valdosta State College (Valdosta State College, 1983)
CHANGE, a word which reflects progress and adventure. How we deal with CHANGE will mold our future. CHANGES, within VSC, are the result of the administrations, the faculty, the staff, and the students' determination to make VSC a better college...During the fall of '82, VSC students had a new team to support. Blazer football was a CHANGE that drew many new students to VSC. The enrollment fall '81 was 4,909 students and fall '82 enrollment increased to 5,548 students. This enrollment CHANGE forced numerous commuting students to change their departure time in order to find a parking place (along the cemetery) and to walk long distances to get to classes...
Milestones 1983
A yearbook was published for Valdosta State College from 1925-1977, under the name The Pinecone. From 1981-1987, a yearbook was published called Milestones. Valdosta State University had three names during this period, Georgia State Womans College, 1925-1950; Valdosta State College, 1950-1993; and Valdosta State University 1993-present.
Keywords: yearbook; Americana; University History; Blazers